Preschoolers’ leadership-followership communication in outdoor pretend play on a child care playground - Kim, Soomin (Kansas State University, 2021)
Leadership begins to develop during early childhood, positively impacting children’s leadership trajectory. Social pretend play provides enriched environments for multiple cognitive and social purposes. The quality and sustainability of children’s social pretend play depends on the process including children’s back and forth proposals and responses about the play frames. Proposing and responding to play ideas with metacommunication use, leadership-followership interactions during pretend play engagement are required in which the leaders and followers are interdependent to effectively move play frames forward. The purpose of this study was to examine the use of metacommunication strategies and leadership/followership processes expressed in social pretend play. A conceptual framework was built on the works by Murphy and Johnson (2011) and Liu et al. (2020) on leadership development and Vygotsky’s work of pretend play during early years, describing the dynamic nature of leadership process within social pretend play. Results indicated that children’s use of metacommunication in social pretend play varies by what contents and to whom they are communicating. Results also showed how much the factors of interest – children’s use of metacommunication, group characteristics for gender, and the role of followership - may impact children’s successful pretend play.
Keywords: Pretend play; Metacommunication; Leadership development; Early childhood